The interpole motor - Goheen, Geo G.; Welsh, Chas R. (My University, 1908)
Introduction: Among the many improvements that have been embodied in the construction of direct current motors, none are of more importance than the interpole, the feature of which did not become general until the last few years. The general idea of providing a special field for the purpose of producing spark-less commutation, is an old one, but it is only recently that designers have gone to providing the extra pole pieces to effect the result.
Citation: Goheen, Geo G. and Welsh, Chas R. A discussion and plans for remodeling the hydraulic lighting plant at Chapman, Kansas. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Motors; Engineering; Electricity; Kansas; Graduating theses; Senior theses; Theses